Genetic correlates of wall shear stress in a patient-specific 3D-printed cerebral aneurysm model. (12th April 2019) - Levitt, Michael R; Mandrycky, Christian; Abel, Ashley; Kelly, Cory M; Levy, Samuel; Chivukula, Venkat K; Zheng, Ying; Aliseda, Alberto; Kim, Louis J
Abstract : Objectives: To study the correlation between wall shear stress and endothelial cell expression in a patient-specific, three-dimensional (3D)-printed model of a cerebral aneurysm. Materials and methods: A 3D-printed model of a cerebral aneurysm was created from a patient's angiogram. After populating the model with human endothelial cells, it was exposed to media under flow for 24 hours. Endothelial cell morphology was characterized in five regions of the 3D-printed model using confocal microscopy. Endothelial cells were then harvested from distinct regions of the 3D-printed model for mRNA collection and gene analysis via quantitative polymerase chain reaction (qPCR.) Cell morphology and mRNA measurement were correlated with computational fluid dynamics simulations. Results: The model was successfully populated with endothelial cells, which survived under flow for 24 hours. Endothelial morphology showed alignment with flow in the proximal and distal parent vessel and aneurysm neck, but disorganization in the aneurysm dome. Genetic analysis of endothelial mRNA expression in the aneurysm dome and distal parent vessel was compared with the proximal parent vessels. ADAMTS-1 and NOS3 were downregulated in the aneurysm dome, while GJA4 was upregulated in the distal parent vessel. Disorganized morphology and decreased ADAMTS-1 and NOS3 expression correlated with areas of substantially lower wall shear stress and wall shear stress gradient in computational fluid dynamics simulations. Conclusions: Creating 3D-printed models of patient-specific cerebral aneurysms populated with human endothelial cells is feasible. Analysis of these cells after exposure to flow demonstrates differences in both cell morphology and genetic expression, which correlate with areas of differential hemodynamic stress.